The Effect of Ladder Drill and Zigzag Run Training on the Agility of Taekwondo Athletes Aged 8- 12 Years - Pratiwi, Nandhini Bintang; Suyoko, Andri; Yudhistira, Dewangga; Antoni, Muhamad Fauzi (JSES : Journal of Sport and Exercise Science, 2026)
Purpose: The study aims to determine the effect of Ladder drill and Zigzag run training on the agility of taekwondo in aged 8-12 years White Tiger Club Mojokerto and to compare the effectiveness of the two methods. Materials and Methods: The study uses a two-group pre-test post-test design with an experimental approach, conducted at the White Tiger Club Mojokerto for 18 meetings. The research subject was all 10 Taekwondo in aged 8-12 years (total sampling), divided using the matched subject ordinal pairing technique into group A: Ladder drill (n=5) and group B: Zigzag run (n=5). The data collection instrument used the Agility T-test. Data analysis included the Shapiro-Wilk normality test, Levene’s Test homogeneity test, Paired Sample T-test, Paired Sample Effect Size (Cohen’s d), and Independent Sample T-test. Result: The results showed that Zigzag run training had a significant effect on increasing agility (p=0,049; Cohen’s d=1,254). Ladder drill training showed positive changes but was not statistically significant (p=0,069; Cohen’s d=1,102). There was no significant difference between the two groups in the post-test (p=0,326). Conclusion: It was concluded that Zig-zag run was more effective in improving the agility of taekwondo in aged 8-12 years because of its relevance to the kyourugi movement pattern.